The impact of the hierarchical medical system on medical resource allocation in China - Liping Fu; Ruizhen Wang; Yu Dong (Scientific Reports)
Abstract The disparity in medical resource distribution across regions poses a significant challenge to healthcare reform in China. To address this, China has introduced the hierarchical medical system (HMS). This study evaluates the HMS’s impact on the equitable distribution of medical resources. We employ the Theil index to quantify the equalization of resources among cities within provinces and use a multi-period difference-in-differences model to assess the HMS’s influence. Our findings indicate that the HMS has significantly contributed to the equal distribution of medical material resources, although its effect on medical human resources is less pronounced. Additionally, we explore the influencing factors of the HMS from the perspective of supply and demand and find that it is more effective in areas with abundant resources and high demand for high-level medical services. More importantly, the HMS has played an important role in mitigating medical disparities in regions with unbalanced economic statuses. These insights are instrumental for policymakers, guiding the evolution of healthcare reforms and the refinement of the HMS to achieve the objective of universal health coverage.